Choosing a methodological base for forming and accounting for the construction costs of a gas well at the final stage of field development (Nexo Revista Científica, 2021)
The article introduces the problems of choosing a methodological base for forming and accounting costs during well construction, taking into account the intensification of gas inflow at the final stage of field development. The main methods that allow taking into account the costs of drilling operations are outlined. The main costs that need to be taken into account when designing fields with hard-to-recover gas reserves are identified and characterized. The main stages of cost formation by construction phases of a gas-producing well are shown, as well as the factors influencing the level and structure of the cost price during the construction of a well are highlighted. The authors consider the classification of cost accounting methods in the context of the comparison criterion and present the possible results of the correct choice of the cost formation method during the construction of a gas well at the final stage of its development.